2006
DOI: 10.1080/00016340600804670
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and the risk of developing hypertensive diseases in pregnancy: what is the effect on HELLP syndrome?

Abstract: Smoking is associated with an 80% reduction of the risk developing HELLP syndrome. However, pregnant women should be advised to quit smoking. Understanding the different effects of smoking in the etiology of each subtype of hypertensive diseases in pregnancy will improve the knowledge of underlying pathophysiological mechanisms and may help in designing more effective prevention and treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…As other known risk factors for hypertensive diseases in pregnancy such as pre-pregnancy BMI or smoking motives for motherhood are differently associated with the risk for pre-eclampsia and HELLP-syndrome [26,37]. This supports that underlying pathophysiology in different types of hypertensive diseases in pregnancy is only partly identical.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…As other known risk factors for hypertensive diseases in pregnancy such as pre-pregnancy BMI or smoking motives for motherhood are differently associated with the risk for pre-eclampsia and HELLP-syndrome [26,37]. This supports that underlying pathophysiology in different types of hypertensive diseases in pregnancy is only partly identical.…”
Section: Discussionsupporting
confidence: 48%
“…to explore the etiological factors in the development of hypertensive disorders in pregnancy. Details of recruitment, exclusion criteria and confounders have previously been reported [22,[26][27][28][29][30]. To summarise, a standardised questionnaire including basic obstetrical and psychosocial questions was sent to 2600 women who addressed the German pre-eclampsia self-help group for information on hypertension in pregnancy and to 1233 control women, who were recruited in seven different hospitals.…”
Section: Methodsmentioning
confidence: 99%
“…This is an important limitation because all of these factors may vary across regions and are also strongly associated with adverse pregnancy outcomes . Higher smoking prevalence among women in rural areas may for example be one explanation for lower prevalence of gestational hypertension . Yet, it is unclear whether the distinct change in prevalence of gestational hypertension during the latter half of the study period reflects a similar change in smoking across areas.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, in the study of Leeners et al (1), there were only 13 pregnancies with chronic hypertension involved. Therefore, they excluded this study group from further analysis.…”
mentioning
confidence: 97%
“…We read with interest the article by Leeners et al (1) in the October 2006 issue of Acta Obstetricia et Gynecologica Scandinavica . They investigated the role of smoking in the development of HELLP syndrome, pre‐eclampsia and gestational hypertension, and found that smoking during pregnancy significantly decreased the risk of HELLP syndrome (adjusted odds ratio (OR): 0.19; 95% confidence interval (CI): 0.08–0.43), HELLP syndrome + pre‐eclampsia (adjusted OR: 0.33; 95% CI: 0.17–0.63), pre‐eclampsia (adjusted OR: 0.46; 95% CI: 0.26–0.8), and tended to decrease the risk of gestational hypertension (adjusted OR: 0.66; 95% CI: 0.41–1.08).…”
mentioning
confidence: 99%